Penguatan Kesadaran Perilaku Hijau Bagi Masyarakat Desa Bhuana Jaya Menuju Desa Wisata Hijau Berkelanjutan - Syilvia Mariya R; Ummi Nadroh; Tuti Wediawati (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2026)
Tourism plays an important role in driving economic growth, but it also has the potential to cause negative impacts on the environment if it is not accompanied by green behavior awareness. Bhuana Jaya Village, Kutai Kartanegara Regency, East Kalimantan, has great potential to be developed as a sustainable green tourism village, but faces the challenge of low public awareness of environmentally friendly behavior. This outreach activity aims to increase community awareness and understanding, particularly among the PKK and POKDARWIS groups, regarding the application of green behavior in daily life and in the management of tourism villages. The methods used were outreach and interactive discussions held on September 3 and 14, 2025, accompanied by evaluations through pre-tests and post-tests. The results of the activity showed a significant increase in participants' understanding, with an average increase of 71% in the PKK group and 56.92% in the POKDARWIS group. The active participation of participants in the discussion and their emotional and cognitive involvement during the activity further strengthened the effectiveness of the socialization method. This activity confirms that the implementation of green behavior not only supports environmental sustainability but also serves as a strategic foundation for the development of sustainable green tourism villages.